CT Measurement of Cerebral Venous Sinus Attenuation Using Hounsfield Unit for Non-Invasive Diagnosis of Anaemia - Surendhar, Surendhar; Kumar, Tharun; Jayaiswarya, Jayaiswarya; Vayshak, Vayshak; Deepika, Deepika; Ilankathir, Ilankathir; Divya, Divya; Rajkumar, Rajkumar (Journal of Neonatal Surgery, 2025)
Background: Computed Tomography (CT) is a widely used imaging modality for evaluating brain structures, including cerebral venous circulation. The attenuation of cerebral veins, measured in Hounsfield Units (HU), can provide crucial insights into various neurological conditions. This non-invasive technique has gained attention as a potential diagnostic tool for assessing cerebral venous thrombosis (CVT), increased intracranial pressure, and blood-brain barrier disruptions. Objective: To determine the correlation between computed tomography attenuation of the cerebral venous sinuses and haemoglobin level with the goal of detecting anaemia Methods: This is the prospective study of 60 patients with traumatic elbow pain, suspected with occult fracture and fat pad sign, patient including RTA, Assault injuries, Sports injuries and other trauma occurs in elbow. All the patients in this study underwent x- ray. Results: Among 60 patients, we measured the Hounsfield unit from the transverse sinus of each patient. Then the HU value is correlated with the haemoglobin concentration from patient’s blood report. It clearly shows 81% of patient were anaemic when their HU value of 32-35 were correlated with haemoglobin concentration. Conclusion: The integration of CT- based hemoglobin estimation could revolutionize the approach to diagnose anemia making it quicker, less invasive and more accessible benefiting both patients and healthcare providers.